Familial Aggregation of Urinary Tract and Bone Tumors: Searching for a Syndrome. (20th May 2012) - Frings, Andreas; Geigl, Jochen B.; Liegl-Atzwanger, Bernadette; Leithner, Andreas
Abstract : Positive family anamnesis is an important risk factor for cancer, and therefore further investigations need to be done if familial aggregation of cancer is observed. Due to a rare combination of urinary tract and bone tumors occurring in the family presented herein we hypothesized a hereditary predisposition and thus, Li-Fraumeni syndrome was considered to be the most likely differential diagnosis. To confirm Li-Fraumeni syndrome, we set out to investigate this case by analyzing the tumor suppressor gene p53 . However, taking into account all the diagnostic results obtained, Li-Fraumeni syndrome could not be confirmed, but there is still uncertainty regarding a definitive diagnosis.